Country versus sector influences and financial analysts' specialization - Sonney, Frédéric (My University, 2007)
This thesis is made of three distinct chapters. The second and third chapters constitute the core of this work. Both focus on financial analysts and their performance depending on whether they are specialized along country or sector lines. The first chapter sets the stage of the analysis. It presents and evaluates the relative strength of country and sector factors in stock returns. Short abstracts of these three chapters appear below. Chapter 1 This paper investigates the relative influences of industrial and country factors in international stock returns. Until very recently, academic research has consistently found that country factors dominate industrial factors. This result is in contradiction with practitioners beliefs. This paper re-examines this issue by analyzing a sample of more than 4000 stocks quoted in 20 developed countries. We find that on average the country effect still dominates stock returns over the period 1997-2000. This result has to be interpreted with caution though, as an analysis that allows for time-varying relative influences demonstrates the rapidly increasing impact of industry effects in recent times. We find, in particular, that this trend is common to all 20 developed countries considered and not only to those that are member of the European Monetary Union. We interpret this result as evidence of the increasing globalization of international equity markets. Chapter 2 Brokerage houses normally structure their research activities along either country or sector lines. I investigate whether organizational structure affects the quality of financial analysts’ earnings forecasts. Specifically, I compare the performance of country-specialized financial analysts with that of sector-specialized financial analysts. The former issue forecasts considerably more accurately than the latter. Country specialists benefit from an informational advantage over sector specialists. A superior knowledge of country-specific factors, as well as geographical proximity between analysts and the firms they cover, are significant determinants of this advantage. Chapter 3 Brokerage houses usually organize their research activities along country or economic sector dimensions. We evaluate which research structure provides most value to investors. To this end, we study the relative information content of stock recommendations issued by country-specialized analysts versus those issued by sector-specialized analysts. Our findings reveal that the former issue more valuable recommendations. The strength of country-specific commonalities explains at least part of the out performance of country-specialized financial analysts. Surprisingly, while analysts’ geographical location has been shown in the literature to be a determinant of earnings forecast accuracy, it is not a source of a comparative advantage when it comes to stock recommendations.
Thèse de doctorat : Université de Neuchâtel, 2007 ; 1944
Keywords: country factors; sector factors; country specialization; sector specialization; financial analysts; forecast accuracy; stock recommendations; geographic advantage; proximity advantage; local versus foreign